2018
DOI: 10.1186/s12245-017-0161-8
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of emergency department triage using the Emergency Severity Index and independent predictors of under-triage and over-triage in Brazil: a retrospective cohort analysis

Abstract: BackgroundEmergency department (ED) triage is performed to prioritize care for patients with critical and time-sensitive illness. Triage errors create opportunity for increased morbidity and mortality. Here, we sought to measure the frequency of under- and over-triage of patients by nurses using the Emergency Severity Index (ESI) in Brazil and to identify factors independently associated with each.MethodsThis was a single-center retrospective cohort study. The accuracy of initial ESI score assignment was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
131
1
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(158 citation statements)
references
References 29 publications
3
131
1
12
Order By: Relevance
“…Due to the fact that about half of all patients are triaged as moderate acuity [17][18][19][20] and that upgrading the ESI is suggested in the case of "clinical suspicion" [21], we assessed the ESI's predictive validity with and without information gained by PDSR (ESI sub-stratified by addition of PDSR 5 ("patient looks extremely ill"), see Table 4). Surprisingly, substantial differences were found in all ESI categories with relevant mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that about half of all patients are triaged as moderate acuity [17][18][19][20] and that upgrading the ESI is suggested in the case of "clinical suspicion" [21], we assessed the ESI's predictive validity with and without information gained by PDSR (ESI sub-stratified by addition of PDSR 5 ("patient looks extremely ill"), see Table 4). Surprisingly, substantial differences were found in all ESI categories with relevant mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Application to modern civilian use has not been standardized nor validated . Modern civilian triage assessment is a poor or inconsistent tool in the reliable prediction of illness severity . This is related to intra‐ and inter‐observer variation in initial assessment of ED patients, including surgical abdomens .…”
Section: Discussionmentioning
confidence: 99%
“…According to studies [2][3][4][5], under-triage contributes to delays in time-sensitive interventions, morbidity, and mortality. Over-triage, may have indirect but equally harmful effects [6], resulting in diversion of limited time and resources from more urgent patients and inappropriate allocation to less severe patients. In a study [2], the clinical severity of under-triage in the MTS was assessed for a cohort of pediatric patients.…”
Section: Existing Clinical Triage Systemsmentioning
confidence: 99%
“…It was concluded that although infrequent, under-triage could have serious clinical consequences. In another study [6], the frequency of under-and over-triaged patients was measured by nurses using the Emergency Severity Index (ESI). Initial ESI-determined triage priority was classified as inaccurate for 16426 of 96071 patients.…”
Section: Existing Clinical Triage Systemsmentioning
confidence: 99%